Using Information Communication Technologies for Interactive Open and Distance Learning Experiences in the Era of COVID-19 (Comparative & International Education Series, 2021)
The novel Corona Virus also known as COVID-19, triggered a global pandemic with far reaching implications for higher education. In Botswana, like other developing countries, it requires a significant paradigm shift from face-to-face to online teaching and learning. Policymakers and education practitioners resolved to consider online education as an alternative method of delivery to ensure continuity in teaching and learning. It is therefore, against this backdrop that this chapter conceptually explores the use of ICT, in the Fourth Industrial Revolution (4IR) era, to facilitate interaction in an open and distance learning delivery mode. This chapter problematises the fact that though the Ministry of Tertiary Education came up with interventions; societal and educational inequalities between public and privately owned higher education institutions will become more predominant. Using the lens of Gorsky, Caspi and Trumper, the author argues that the noble intent of governments may facilitate further social exclusion and digital divide.